Overexpression of asparaginyl endopeptidase is significant for esophageal carcinoma metastasis and predicts poor patient prognosis - Liu, Xinyang (Oncol Lett, 2018)
Esophageal cancer is one of the most common types of cancer with poor prognosis. The molecular mechanisms of esophageal cancer progression remain unknown. In the present study, the aim was to investigate the clinical significance and biological function of protease asparaginyl endopeptidase (AEP) in esophageal cancer. The expression of AEP in esophageal cancer was examined, and its association with clinicopathological factors and patient prognosis was analyzed. A series of functional and mechanistic assays were performed to further investigate the underlying molecular mechanisms, and functions in esophageal cancer. The expression of AEP was elevated in esophageal cancer tissues, and patients with high AEP expression displayed a significantly shorter survival time compared with those with low AEP expression. In addition, loss of function experiments demonstrated that knockdown of AEP significantly reduced the migration and invasion ability of esophageal cancer cells. Furthermore, the pro-oncogenic effects of AEP in esophageal cancer were mediated by the upregulation of matrix-metalloproteinase 2 and 3. Taken together, the data from the present study indicates that high AEP expression is associated with esophageal cancer progression and AEP is an indicator of poor prognosis in patients with esophageal cancer. AEP therefore, may be considered as a novel prognostic biomarker or potential therapeutic target in esophageal cancer.